A new global data set on farm size distribution by country - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
This is the first stage in the development of spatially-explicit global datasets on farm size distribution for use in targetting analysis. This work had an Altmetric score of 191 and featured widely in the media when published.